Establishment of a cassava (Manihot esculenta Crantz) core collection based on agromorphological descriptors - Bhattacharjee, Ranjana; Dumet, D.; Ilona, Paul; Soyode, F.; Franco, J. (Cambridge University Press, 2012)
International Institute of Tropical Agriculture maintains 2544 cassava accessions (Manihot esculenta Crantz) from 28 countries in its field bank. Being vegetatively propagated, this poses challenges in maintenance in terms of cost as well as in labour requirements. A core collection representing the range of phenotypic diversity present in the entire collection would enhance the conservation aspects and increase the potential for its exploitation in crop improvement programmes. The present study aimed to establish a core collection using 40 agro-morphological traits evaluated at two locations using a different number of accessions in each location. To meet the challenges generated by the types of variables and include maximum diversity in the core collection, a sequential strategy based on five major concepts was used: hierarchical multiple factor analysis allowing the mixture of variables of different kinds; three-way analysis that included the effect of genotype £ environment interaction in the clustering process; linear discriminant function to assign all those individuals who were included in one location but not in the other to the groups that were generated from the common number of accessions evaluated in both locations; and D-allocation method to select samples from each cluster. The representativeness of the core subset to the entire collection was further estimated by comparing means and variances, range, and distances between accessions. The established cassava core collection consisted of 428 accessions that conserved 15% higher phenotypic diversity with no redundancies. The phenotypic diversity represented in this core collection will be a guide to users of cassava germplasm in their crop improvement programmes.